RS Open Journal on Innovative Communication Technologies 2021
DOI: 10.46470/03d8ffbd.275ae770
|View full text |Cite
|
Sign up to set email alerts
|

STBC-assisted OFDM with Subcarrier Power Modulation

Abstract: Orthogonal Frequency Division Multiplexing with Subcarrier-Power Modulation (OFDM-SPM) has recently been proposed as a promising, potential transmission technique for future wireless communications (i.e., 6G and beyond) due to its multiple beneficial characteristics, including higher spectral efficiency, low latency with good reliability while maintaining low complexity. In this paper, the OFDM-SPM technique is compounded with Alamouti space-time block coding (STBC) in a multiple-input-single-output (MISO) set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Besides, CP OFDM has many drawbacks, including high OOBE, as well as orthogonality, which necessitates precise time and frequency synchronization to prevent timing and frequency offsets, which can result in inter-carrier Interference (ICI) [57], and high PAPR, which dismiss the conventional OFDM to be a candidate for a future generation [55], [58]. Researchers have attempted to reduce these drawbacks and enhance the performance of OFDM to be deployed in 6G [59]- [62]. Many research suggested new waveforms, including filtered OFDM (F-OFDM), Generalized Frequency Division Multiplexing (GFDM), Filter-Bank Multicarrier (FBMC), and Universal Filtered Multicarrier (UFMC) to address current and upcoming wireless issues and address the shortcomings of OFDM.…”
Section: ) Orthogonal Multiple Access (Oma)mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, CP OFDM has many drawbacks, including high OOBE, as well as orthogonality, which necessitates precise time and frequency synchronization to prevent timing and frequency offsets, which can result in inter-carrier Interference (ICI) [57], and high PAPR, which dismiss the conventional OFDM to be a candidate for a future generation [55], [58]. Researchers have attempted to reduce these drawbacks and enhance the performance of OFDM to be deployed in 6G [59]- [62]. Many research suggested new waveforms, including filtered OFDM (F-OFDM), Generalized Frequency Division Multiplexing (GFDM), Filter-Bank Multicarrier (FBMC), and Universal Filtered Multicarrier (UFMC) to address current and upcoming wireless issues and address the shortcomings of OFDM.…”
Section: ) Orthogonal Multiple Access (Oma)mentioning
confidence: 99%
“…Filter-Bank Multicarrier (FBMC): It is the waveform candidates that are best suited for use in wireless communications in the future. To overcome the drawbacks of the multicarrier approach, Saltzberg and Chang proposed FBMC in 1971 [72], [62]. Since it is an OFDM advancement [72], FBMC inherits most of the OFDM features.…”
Section: ) Orthogonal Multiple Access (Oma)mentioning
confidence: 99%
“…In Abuqamar, Hamamreh & Abewa (2021) STBC was combined with Orthogonal Frequency Division Multiplexing with Sub carrier-Power Modulation (OFDM-SPM) to analyze combination on a multi-path Rayleigh fading channel. BER and throughput were used as a performance metrics.…”
Section: Related Workmentioning
confidence: 99%
“…Hijazi and Hamamreh [15] suggested signal space diversity as a solution to enhance the system performance through the Rayleigh fading channel where they achieve a gain of more than 5 dB. Abuqamar et al [16] suggested using Alamouti space-time block coding in a multiple-input-single-output over a multipath Rayleigh fading channel to enhance the throughput and BER performance.…”
Section: Introductionmentioning
confidence: 99%